COMPARISON OF CLINICAL ACTIVITY OF PIMECROLIMUS IN PEDIATRIC PATIENTS WITH MILD AND MODERATE ATOPIC DERMATITIS - E.V. Deeva; L.M. Ogorodova; I.A. Deev; I.V. Sheveleva ("Paediatrician" Publishers LLC, 2008)
Atopic dermatitis (ad) is prevalent disease in younger children. Calcium inhibitor pimecrolimus (elidel, cream 1%) is the latest anti-inflammatory drug offered for management of ad. The activity of pimecrolimus was evaluated in open, prospective, randomized, comparison trial, on 60 children (age from 3 months to 7 years) with mild and moderate ad. Pimecrolimus was more effective in management of mild ad on the assumption of regular use of drug (TIS < 17), and topical corticosteroids were effective in patients with moderate ad.Key words: children, atopic dermatitis, pimecrolimus, topical corticosteroids, management.